Proceedings of the 8th International Conference on Communities and Technologies 2017
DOI: 10.1145/3083671.3083690
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Synchronous IVR Radio on Syrian Refugee Health and Community Dynamics

Abstract: With 1,033,513 Syrian refugees adding a strain on the Lebanese healthcare system, innovation is key to improving access to healthcare. Our previous work identified the potential for technology to improve access to antenatal care services and increase refugee agency. Using (1) paper mock ups and a mobile based prototype, (2) process mapping, (3) focus groups and interviews and (4) key informant meetings, we explored the concept of refugee led community radio shows to deliver peerled healthcare. 1 We observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…In his reflection on the principles of human-centered design, Buchanan recommends that human dignity be put center stage from the onset of design processes in order to ensure that technological designs maintain and promote human dignity [8,9]. To do so in refugee contexts entails critical reflection, by both designers and participants, on how a technology may produce tangible outcomes that would benefit refugee communities, such as [14,26,31,32], and in addition mediate and facilitate 'dignified interactions' through the provision of information or through how they configure interactions. Design approaches such as Interaction design [17], Experience Centered Design [30] and Value Sensitive Design [16] , that bring forth refugee perspectives in to the design of humanitarian technologies, may surface experiences in which the maintenance of dignity is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In his reflection on the principles of human-centered design, Buchanan recommends that human dignity be put center stage from the onset of design processes in order to ensure that technological designs maintain and promote human dignity [8,9]. To do so in refugee contexts entails critical reflection, by both designers and participants, on how a technology may produce tangible outcomes that would benefit refugee communities, such as [14,26,31,32], and in addition mediate and facilitate 'dignified interactions' through the provision of information or through how they configure interactions. Design approaches such as Interaction design [17], Experience Centered Design [30] and Value Sensitive Design [16] , that bring forth refugee perspectives in to the design of humanitarian technologies, may surface experiences in which the maintenance of dignity is required.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this paper are a result of engagements with Syrian refugee women residing in informal settlements in rural Lebanon as part of three research projects (n= 87). The first two studies [26,27] explored refugee experiences in accessing healthcare services through engaging with five Syrian refugee communities through focus groups (n=59, P1…P59) and the subsequent piloting and evaluation of a technology that aimed to improve access to healthcare with one of the refugee communities (n=15, P60…P75). Piloting and evaluating the technology entailed nine focus groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fisher et al [22] studied how Syrian youths use connected technology to help others in the Za'atari refugee camp in Jordan, whilst Maitland and Xu [37] found that a large majority (86%) of refugees in the same camp owned a mobile phone. Talhouk et al [50,51] 57]. However, unlike the focus of this cannon of literature that explores the role of mobile technology either during the refugee journey or in the old home country, the focus of our paper differs from this body of work as it looks at mobile phone use in the new country, at a time of changing precarity and where the pressures of old and new homes collide.…”
Section: Mobile Phone Use In Refugee Communitiesmentioning
confidence: 99%
“…They show how the mobile phone becomes a safe space when traditional institutions of safety break down, whilst also illustrating that these spaces come with certain threats and vulnerabilities that reduce the capacity for deliberative decision-making and reflective judgments on the uses of the mobile phone. This is significant as previous studies [2,22,43,51] and humanitarian reports [52] on refugees and mobile phones have focused almost exclusively on the benefits of increased connectivity for this community, with little recognition of the negative aspects that might be fostered by mobile phone use in this context [18]. There is an implicit assumption in the existing body of work that mobile phones enable and promote different personal freedoms and a sense of individual security.…”
Section: Introductionmentioning
confidence: 96%